Development and evaluation of serious games as assistive technology through affordable access multi-devices - Longo, Berthil Borges (2019)
The purpose of rehabilitation processes is to restore a person to a state of optimal functioning. A wide variety of rehabilitation processes consist of repetitive tasks. Thus, Serious Games can be used as a technology to assist in this process by motivating patients to perform the exercises during rehabilitation sessions using a variety of objectives, such as goals or scores to be achieved during the sessions. However, electronic games used in these processes can be commercial games designed with a main purpose of player entertainment, or games created specifically for rehabilitation, whose main purpose is patient rehabilitation. The latter has some advantages over the former because they are specifically designed for this purpose, involving specific rehabilitation knowledge applied in the game development. However, there is some discussion about clinical efficacy and acceptance by users and health professionals involved on this new approach, and how to integrate it into conventional rehabilitation. According to the World Disability Report produced by the World Health Organization, people with disabilities and their families are more likely to suffer economic, educational and social disadvantages than people without disabilities, which is also a reality for most people in Brazil. It is therefore important that new approaches developed are accessible to all, regardless of their social level. The use of affordable access devices in the development and production of such technology reduces its final cost by making it more accessible. Thus, this work addresses the theme Serious Games combined with affordable access devices to spread their use, as well as their evaluation by users, patients and health professionals involved in rehabilitation. In order to do so, Serious Games were created in two modalities: one aimed at being used by health professionals directly with patients undergoing rehabilitation, and another one focused on laboratory research, both involving the use of affordable access devices, all of which are evaluated by specific queries for this purpose.